Pathogenicity and epidemiological survey of fowl adenovirus in Shandong Province from 2021 to 2022 - Wang, Tailong; Meng, Fanliang; Chen, Changxiu; Shen, Yesheng; Li, Peixun; Xu, Jie; Feng, Zhaoyang; Qu, Xiuchao; Wang, Fuyong; Li, Baoquan; Liu, Mengda (Frontiers in Microbiology, 2023)
In recent years, adenoviral diseases such as Hydropericardium Syndrome (HPS) and Inclusion Body Hepatitis (IBH) caused by Fowl adenovirus (FAdV), have become seriously prevalent in China, causing great harm to the current poultry industry. As an important area for poultry breeding in China, Shandong Province has a series of complex and diverse FAdV serotypes. The predominant strains and their pathogenic characteristics are not yet reported. Therefore, a pathogenicity and epidemiological survey of FAdV was conducted. The results showed that the local dominant serotypes of FAdV epidemic are FAdV-2, FAdV-4, FAdV-8b and FAdV-11. Their lethal rate to 17-days-old specific-pathogen-free (SPF) chicks varies from 10% to 80%. The clinical signs included mental depression, diarrhea and wasting. The maximum duration of detoxification was 14 days. The highest incidence in all infected groups was on days 5-9, and then gradual regression thereafter. The most pronounced symptoms were in FAdV-4 infected group, which shows pericardial effusion and inclusion body hepatitis lesions. This study further enriched the current epidemiological data of FAdV in Shandong flocks and evaluated the pathogenicity of different serotypes. It provided a theoretical basis for FAdV vaccine development and comprehensive prevention and control.